Civil society: new forms of collective action - Σημίτη Μαριλένα (SPOUDAI Journal of Economics and Business, 2024)
This paper presents the main attributes of New Social Movements, which emerged in Western Europe and the USA during the 70's. New Social Movements presented a significant rupture with the economic and political model, which prevailed in post-war European societies. However, their innovative elements were still bound to the historical cycle they represented. The significant political changes during the 80's were coupled with the gradual demise of New Social Movements and the rise of new forms of collective action in civil society (e.g. Non-Governmental Organisations). JEL Classification: Z00